A Theory of Acquisition Markets: Mergers versus Tender Offers, and Golden Parachutes - Berkovitch, Elazar; Khanna, Naveen (Review of Financial Studies, 1991)
We develop a model of the acquisition market in which the acquirer has a choice between two takeover mechanisms: mergers and tender offers. A merger is modeled as a bargaining game between the acquiring and target firms; whereas a tender offer is modeled as an auction in which bidders arrive sequentially and compete for the target. At any stage of the bargaining game the acquiring firm can stop negotiating and make a tender offer. In equilibrium, there is a unique level of synergy gains below which the acquiring firm makes only a merger attempt as it expects to lose in the competition resulting from a tender offer. For synergy gains above this level, tender offers can occur. However, to get tender offers, target shareholders must give their managers golden parachutes that give higher payoffs in tender offers than in mergers.